Evaluating the prevalence of nephrolithiasis in kidney transplant recipients admitted to Imam Khomeini Hospital in Urmia in 2018-2019. - Tayyebi Azar, Ali; Khezri, Sima; Mokhtarzadehazar, Peyman; Emamverdi, Mehdi (Archives of Men's Health, 2023)
Introduction: Nephrolithiasis is almost common urological disease in the world that involves near 10 percent of adult population. Several researches are demonstrative of increasing prevalence and incidence of nephrolithiasis in industrial societies, because of changing the life style, food regimen and obesity that is very common. Though prevalence of nephrolithiasis in grafted kidney is rare, but because of importance of effects after grafting or graft rejection is needed to attention and study. Methods: In this research incidence of nephrolithiasis and the difference of it before and after the kidney transplantation in graft receiver of kidney in Urmia Imam Khomeini hospital for two years in 2018-2019 has studied, and followed after one year. Relation between age, education level, and sex have been evaluated too. Results: In this study 32 receiver of kidney transplant have been studied. Among this 32 patient 3 cases had nephrolithiasis after transplantation that they didn’t have any history of nephrolithiasis, And 3 cases had history of nephrolithiasis that after transplantation no kidney stone was seen (P<0.05).Higher prevalence of nephrolithiasis was significantly related to higher level of education (p<0.05), but age and sex was not significantly different in two groups (P>0.05). Conclusion: It’s concluded that the main reason of nephrolithiasis is the kidney organ that can make stone in the new body, and level of education was higher in the nephrolithiasis group (affected or have the history) than the healthy group.